Intratumor Heterogeneity of K-Ras and p53 Mutations among Human Colorectal Adenomas Containing Early Cancer - Walter Giaretti; Barbara Macciocu; Elio Geido; Mario Hermsen; Cindy Postma; Jan Baak; Richard Williams; Gerrit Meijer (Analytical Cellular Pathology)
The molecular pathways and the timing of genetic events during human colorectal carcinogenesis are still not fully understood. We have addressed the intratumor heterogeneity of the mutational status of the k‐ras oncogene and of the p53 oncosuppressor gene during the adenoma–carcinoma sequence by investigating 26 human colorectal adenomas containing early cancer. An intratumor comparative analysis was obtained among the adenomatous and carcinomatous component pairs. Additionally, we have analyzed 17 adenomas having cancer in the near vicinity. The adenomatous components of the adenomas containing early cancer and the adenomas having cancer in the near vicinity had comparable frequencies for k‐ras mutations (28 and 47%) but different for p53 mutations (52 and 7%, p‐value = 0.01). Interestingly, the adenomatous and carcinomatous components of the adenomas containing early cancer were rarely heterogeneous for the k‐ras mutational status (only in 13% of the cases) but were characterized by heterogeneity of the p53 status in 59% of the cases (p‐value < 0.01). In addition, the mutations of p53 for the adenomatous components of the adenomas containing early cancer were statistically significantly associated with severe dysplasia (p-value = 0.01). Intratumor homogeneity of k‐ras status during the human colorectal adenoma–carcinoma sequence suggests that the role of k‐ras is more related to tumor initiation than to tumor progression. On the contrary, intratumor heterogeneity of p53 mutations indicates that the type of the p53 mutations may also be relevant for selection and expansion of new subclones leading to tumor progression.